Potensi dampak pembangunan jalan tol terhadap sektor pariwisata Yogyakarta: Analisis input-output dan ketimpangan - Muhammad Viktar Sabilillah Tafarel; Ira Rahayuningtyas (Regional Development Information Center, Universitas Sebelas Maret, 2026)
Transportation infrastructure development plays a crucial role in promoting regional development and enhancing the performance of leading economic sectors. In the Special Region of Yogyakarta, the development of the National Strategic Projects (PSN), namely the Solo–Yogyakarta–YIA and Yogyakarta–Bawen toll roads, is expected to improve regional connectivity and support tourism development. This study aims to analyze the potential economic impacts of toll road development on the Yogyakarta region, with a particular focus on the tourism sector and regional inequality. The study applies input-output analysis to examine intersectoral linkages and the Williamson Index to assess regional economic disparities. The analysis utilizes regional input-output tables and relevant regional economic data corresponding to the development planning period. The results indicate that the construction sector and most tourism-related sectors are classified as first-priority sectors, characterized by high backward linkages and dispersion indices. An infrastructure investment shock of Rp 18.997 trillion in the construction sector generates significant multiplier effects on output, investment, and employment in tourism-related sectors. Furthermore, Williamson Index analysis suggests that toll road development has the potential to reduce regional economic disparities if infrastructure benefits are distributed equitably. These findings highlight that toll road development functions not only as a driver of regional economic growth but also as a catalyst for inclusive and sustainable tourism development in Yogyakarta.